Pengaruh Pemberian Cuka Apel 'A' terhadap Kadar MDA Hepar Tikus Wistar Jantan yang Diinduksi Parasetamol Dosis Toksik - Niki Niki Rahmawati; Sugiyanta Sugiyanta; Elly Nurus Sakinah (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
High dose of paracetamol is metabolized by cytochrome P-450 become free radical N-acetyl-p-benzoquinoneimine (NAPQI) but liver Glutathione (GSH) is not adequate to change it become nonreactive metabolite so that NAPQI bind to unsaturated fatty acid of cell membrane, causing lipid peroxidation and increase liver Malondialdehyde (MDA). 'A' apple vinegar contains anthocyanin with an antioxidant effect by electron donor to NAPQI and acetic acid to improve liver GSH level. The aim of research was to investigate the effect of 'A' apple vinegar on the rat liver MDA induced by toxic dose of paracetamol. Research groups consist of normal control (CMC Na 1% 1 ml for 14 days), negative control (CMC Na 1% 1ml for 14 days + paracetamol 291.6 mg/200gBW on the day 12nd,13rd,14th), and treatment group ('A' apple vinegar 0.4 ml/150gBW for 14 days + paracetamol 291.6 mg/200gBW on the day 12nd,13rd,14th). Liver MDA was measured on the day 15th with competitive ELISA. The average of normal control group was 21.58 ng/ml, negative control group was 70,71 ng/ml, treatment group was 37,67 ng/ml. One way ANOVA and Post hoc LSD test showed significantly differences between all groups (p<0,05). It can be concluded that 'A' apple vinegar had an effect on the liver MDA induced by toxic dose of paracetamol. Keywords: Paracetamol, NAPQI, MDA, 'A' apple vinegar, antioxidant